Anatomy of the culm of Dendrocalamus asper (Bambusoideae: Bambuseae) to determine its mature status: Case study of its use in construction - Tania Cerrón-Oyague; Eduardo Ruiz-Sanchez; Gonzalo Torres-Zules; Rolando Montenegro-Muro; Manuel Chavesta-Custodio; Farut Varón-Virguez (Advances in Bamboo Science)
Bamboo culms are a renewable natural resource widely used in housing construction. The structural characteristics of bamboo culms vary depending on their maturity state and the influence of aging on maturation, particularly regarding strength properties. This case study focuses on evaluating the state of maturity of bamboo material (strips/slats) from the species Dendrocalamus asper. The objective was to determine its maturity state and establish a reliable criterion for its classification and use in construction. To assess culm maturity, mature culms were identified as those where the cells near the vascular bundles were completely filled with fibers, as indicated by a reddish colouration when stained with safranin, with no blank spaces remaining. Anatomical sections of D. asper culm samples were prepared using a microtome and stained with safranin. Our results showed that 60 % of the analyzed material exhibited an immature condition. This case study provides a methodology for verifying bamboo material for use in construction, which can be applied in other cases where the maturity of bamboo is uncertain.